2012
DOI: 10.1007/s11999-011-1992-x
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients With Traumatic Recurrent Anterior Shoulder Instability Have Generalized Joint Laxity?

Abstract: Background A number of studies suggest a relationship between generalized joint laxity (GJL) and increased risk of some musculoskeletal injuries. However, there are conflicting data on the association between GJL and traumatic recurrent shoulder instability (RSI). Questions/purposes We therefore asked whether the incidence of GJL in patients with RSI was greater than that in a control group. Methods We preoperatively determined GJL with a Beighton score in 100 male patients arthroscopically treated for RSI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Several decades ago, GJL was regarded as an asymptomatic disorder; however, it has recently been shown that GJL may be associated with specific disorders and clinical manifestations [11,13,16]. Orthopedic surgeons have investigated the relationship between GJL and acute anterior shoulder dislocation or ligament injury; GJL may also be a causative factor for LDH [5][6][7][8]. Previous studies have recognized that the recurrence of disc herniation after surgical discectomy for p-LDH is closely associated with the presence of GJL at baseline [2,14,15,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several decades ago, GJL was regarded as an asymptomatic disorder; however, it has recently been shown that GJL may be associated with specific disorders and clinical manifestations [11,13,16]. Orthopedic surgeons have investigated the relationship between GJL and acute anterior shoulder dislocation or ligament injury; GJL may also be a causative factor for LDH [5][6][7][8]. Previous studies have recognized that the recurrence of disc herniation after surgical discectomy for p-LDH is closely associated with the presence of GJL at baseline [2,14,15,18].…”
Section: Discussionmentioning
confidence: 99%
“…anterior cruciate ligament injury [5][6][7][8][9]. The term GJL was first used in 1967 to describe musculoskeletal symptoms in the presence of joint laxity that were not attributable to other disease [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinicians have investigated GJL due to its relationship to diseases such as acute anterior shoulder dislocation and ligament injury. 5 , 15 , 16 , 17) Likewise, GJL may be a causative factor for LDH. 13) Previous studies have determined that lower back pain, accelerated disc degeneration, and the recurrence of disc herniation following discectomy for primary LDH are closely related to the presence of GJL at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in a population of professional rugby players that shoulder translation or anterior laxity is associated with increased risk of dislocation. 43 Additionally, baseline testing for shoulder instability, strength, range of motion, and structural measurements demonstrate that the most significant structural risk for posterior shoulder injury is increased glenoid retroversion. 38 Screening processes and targeted injury prevention strategies should continue to be developed using identifiers for individuals at risk for shoulder injury.…”
Section: Ligament Injury-associated Joint Instabilitymentioning
confidence: 99%